Networked Social Reproduction: Crises in the Integrated Circuit - Elise Danielle Thorburn (tripleC: Communication, Capitalism & Critique)
This paper argues that the means of communication are sites for, and aspects of, social reproduction. In contemporary capitalism, motivated as it is by new, networked digital technologies, social reproduction is increasingly virtualised through the means of communication. Although recent political struggles have demonstrated how networked technologies can liberate social reproduction from the profit motive and from commodifying impulses, the tendency is to invoke and accelerate socially reproductive crises—crises in the capacity to reproduce ourselves both daily and intergenerationally. These crises have psychic and corporeal impacts, and intensify Tronti’s “social factory” thesis of capital’s technical composition. In order to develop modes and means of liberatory communication in the integrated circuit it is necessary to untangle and chart both the pathways and outcomes of the crises networked social reproduction invokes.